Analysis of the Impact of Lifestyle Changes on Fast Food Consumption Trends Among Millennial: Implication for Educational Awareness - Imelia, Venny Juwita; Ulfa, Aulia; Ingtyas, Fatma Tresno; Ginting, Laurena (Journal Corner of Education, Linguistics, and Literature, 2024)
The culinary business is currently experiencing rapid growth, marked by the emergence of food businesses, both local, national, and internationally recognized brands. One of the food trends that is popular among the millennial generation is fast food. The method used in this study is meta-analysis, which involves analyzing and combining data from 16 journals obtained through Google Scholar that relate to culinary trends among millennials. Consumption of fast food has become a trend among young people, especially millennials, due to its practicality, speed, and modern appeal. The results of this study show that excessive consumption of fast food can lead to various health risks such as obesity, diabetes, hypertension, and other degenerative diseases.